2018
DOI: 10.1080/00224545.2018.1453467
|View full text |Cite|
|
Sign up to set email alerts
|

The burden of online friends: The effects of giving up Facebook on stress and well-being

Abstract: People occasionally choose to cut themselves off from their online social network by taking extended breaks from Facebook. This study investigated whether abstaining from Facebook reduces stress but also reduces subjective well-being because of the resulting social disconnection. Participants (138 active Facebook users) were assigned to either a condition in which they were instructed to give up Facebook for 5 days or continue to use Facebook as normal. Perceived stress and well-being, as well as salivary cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 36 publications
1
59
5
Order By: Relevance
“…They often find inconclusive effects that, however, suggest a tentative positive association between limiting social media use and well-being. A study showed that those participants told to refrain from using Facebook for 5 days exhibit lower cortisol levels: but they also reported decreased life satisfaction [65]. In another study, those participants asked not to go on Facebook for a week showed increased life satisfaction, especially if they were heavy users [59].…”
Section: Methodological Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They often find inconclusive effects that, however, suggest a tentative positive association between limiting social media use and well-being. A study showed that those participants told to refrain from using Facebook for 5 days exhibit lower cortisol levels: but they also reported decreased life satisfaction [65]. In another study, those participants asked not to go on Facebook for a week showed increased life satisfaction, especially if they were heavy users [59].…”
Section: Methodological Improvementsmentioning
confidence: 99%
“…Such conflicts could be the result of the studies' low quality. Many experimental designs did not limit all social media use and most studies found it difficult to obtain good levels of participant compliance [2,59,65]. Furthermore, there is a potential for bias in participant selection: those potential participants who are not as reliant on social media to obtain positive outcomes might be more likely to take part in studies asking for them to give up social media.…”
Section: Methodological Improvementsmentioning
confidence: 99%
“…Research on SM abstinence is scarce and the aforementioned studies focused on Facebook use rather than multiple SM platforms [ 45 ] and used self-reports to measure SMU [ 25 ]. As multiple SM platforms are now primarily accessed through portable smartphones [ 12 ] and SMU self-report measures tend to be subjective and biased [ 46 , 47 , 48 ], multiple SM platform use needs to be studied with more objective measures over time.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to increased time on SNS taking time away from other activities that may engender improved subjective wellbeing such as exercise, productive pursuits (e.g., work, education), or direct social interactions. Related to anxiety, perceived life stress has been consistently linked to use of SNS (e.g., Vanman, Baker, & Tobin, 2018), and other studies have shown a positive correlation between poor physical health appraisal and symptomology with increased SNS use (e.g., Dibb, 2019). Taken together, these findings suggest major mental, social, and physical health disturbances coinciding with increased daily combined SNS use, and raise the question regarding effects of specific SNS on user health and wellbeing.…”
Section: Social Networking Sites and Health Among Young Adultsmentioning
confidence: 88%
“…Facebook, the most researched of all SNS, is primarily textbased and broadcasted to a wide audience of "friends." Increased Facebook use has been specifically linked to many healthrelated outcomes including loneliness (e.g., Song et al, 2014), low subjective wellbeing (e.g., Tromholt, 2016), poor health behaviors (e.g., Dibb, 2019), and high perceived stress (e.g., Vanman et al, 2018), although some studies suggest positive outcomes like emotional support (Ellison, Steinfield, & Lampe, 2007).…”
Section: Specific Social Networking Sites and Healthmentioning
confidence: 99%